2001
DOI: 10.1054/bjoc.2000.1635
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional down-regulation of the retinoblastoma protein is associated with differentiation and apoptosis in human colorectal epithelial cells

Abstract: SummaryThe aim of this study was to investigate the regulation of Rb protein expression in relation to increased differentiation and induction of apoptosis in colonic epithelial cells. In vivo, Rb protein expression was found to be down-regulated towards the top of the normal colonic crypt, coincident with the region of differentiation and apoptosis, but highly expressed in colonic carcinoma tissue. Using in vitro models to study the regulation of Rb expression in pre-malignant colonic epithelial cells, we hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
13
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 51 publications
4
13
0
Order By: Relevance
“…The early decrease in body fat content is probably not due to a differentiation defect of adipose tissue precursors, because such cells require a longer period to achieve full terminal differentiation. In agreement with previous studies in which low levels of pRb coincide with an enhanced rate of apoptosis (30)(31)(32)(33), a similar increase in the rate of apoptosis was also found in pRb-deficient MEFs as compared with control MEFs.…”
Section: Discussionsupporting
confidence: 92%
“…The early decrease in body fat content is probably not due to a differentiation defect of adipose tissue precursors, because such cells require a longer period to achieve full terminal differentiation. In agreement with previous studies in which low levels of pRb coincide with an enhanced rate of apoptosis (30)(31)(32)(33), a similar increase in the rate of apoptosis was also found in pRb-deficient MEFs as compared with control MEFs.…”
Section: Discussionsupporting
confidence: 92%
“…prb is able to act as a survival factor in colonic epithelial cells by suppressing apoptosis.the overexpression of prb in colorectal tumor cells can cause a loss of sensitivity to apoptotic signaling, resulting in aberrant cell survival and resistance to therapy (31). our study showed that a trend for a higher pathological cr rate was observed in tumors with a negative prb expression (table I).…”
Section: Discussionsupporting
confidence: 49%
“…Most interesting is our observation that activation of PPARg in differentiated colon cells, where RB is almost absent, induces apoptosis. This mimics the in vivo situation, since PPARg is strongly expressed (Lefebvre et al, 1999) and RB is almost absent (Guy et al, 2001;Yamamoto et al, 1999) in differentiated epithelial cells found at the top of the villi in the colon. One of the consequences of the high ratio of PPARg to RB expression in the villi is the stimulation of apoptosis, which contributes to cell turn-over in normal colon.…”
Section: Pparg Rb and Apoptosismentioning
confidence: 67%